Building Social Welfare Through Social Security Based on The SocioEconomic Justice During COVID-19 Pandemic Crisis - Muhammad Rafi’i; Zaid (Jurnal Sosial Humaniora, 2021)
The purpose of this paper is to examine and analyze based on the principles ofsocial and economic justice on how to grow prosperity during a recession inthe midst of the COVID-19 pandemic as it is today through the strategy ofproviding social security to affected communities. By involving literaturereview or normative research methods along with a qualitative approach andlegislation, this study found that the law on the security system stipulates thatsocial security includes six forms of social security, including health security,work accident security, old-age security, pension security, death security, andjob loss security. it's just that the problem is for those who do not pay dues orparticipate in the government's social security program. Their welfare mustalso be considered as mandated by the constitution of the 1945 Constitution.And in the principle of socio-economic justice, social security must beprioritized for the poor and underprivileged who are felt to be in more socialneed to achieve equity and social welfare.